Parasitoid Telur pada Hama Kubis Plutella xylostella (L.) (Lepidoptera : Yponomeutidae) - Araz Meilin; Purnama Hidayat; Damayanti Buchori; Utomo Kartosuwondo (Buletin Hama dan Penyakit Tumbuhan, 2000)
Egg parasitoids of the diamonback mont, Plutella xylostella (L.) (Lepidoptera : Yponomeutidae) have never been reported in Indonesia. In this study, eggs of P.xylostella were collected from cabbage planation in Cisarua-Bogor, Ciloto-Cianjur, Cikole-Lembang (West Java), Tawangmangu (Central Java), and Malang (East Java). Three species of parasitoids were colleted from all areas, Trichogrammatoidea armigera Nagaraja emerged from eggs colledted from Cisarua-Bogor, Cikole-Lembang, and Ciloto-Cianjur, and Trichogramma flandersi Nagaraja and Nagarkatti (Hymenoptera : Trichogrammatidae) was only found from the eggs collected from Tawangmangu. The morphological character of the parasitoids are discussed